2003
DOI: 10.1051/rnd:2003020
|View full text |Cite
|
Sign up to set email alerts
|

II. Quantitative aspects of phosphorus absorptionin ruminants

Abstract: -Phosphorus absorption in ruminants was analysed from a database described in a previous article. For common values of ingested phosphorus (2.5-5.0 g·kg -1 of DM), 0.73 of dietary phosphorus is absorbed. The remaining variability is probably due to phosphorus quality. Phosphorus absorbed from silage, cereal, cereal by-products and hay differs greatly. The current true absorption coefficient used to calculate daily phosphorus supply is a constant value in the current systems and often it underestimates the true… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
25

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 58 publications
1
15
0
25
Order By: Relevance
“…The difference between intake and excretion of calcium was 12.20, 61.65, 74.22 and 64.10% for the doses 0.0, 0.8, 1.6 and 2.4%, respectively, whereas for the phosphorus levels, the excretion was greater than the intake, possibly because there was some imbalance between the minerals and also because of the greater amounts of endogenous phosphorus losses. Louvandini & Vitti (2007), Bravo et al (2003a) and Dias et al (2007) commented that the increase in the phosphorus content in the sheep diet increases its absorption and excretion through the feces, which is the preferential pathway for elimination. Louvandini & Vitti (2007) claimed that the phosphorus consumed and that present in the urine are associated with the stabilization of the endogenous fecal loss, associated with the excess material ingested and the type of feed ingested, since the greater the effective fiber content ingested, the more salivation and excretion of phosphorus through the feces (Bravo et al, 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…The difference between intake and excretion of calcium was 12.20, 61.65, 74.22 and 64.10% for the doses 0.0, 0.8, 1.6 and 2.4%, respectively, whereas for the phosphorus levels, the excretion was greater than the intake, possibly because there was some imbalance between the minerals and also because of the greater amounts of endogenous phosphorus losses. Louvandini & Vitti (2007), Bravo et al (2003a) and Dias et al (2007) commented that the increase in the phosphorus content in the sheep diet increases its absorption and excretion through the feces, which is the preferential pathway for elimination. Louvandini & Vitti (2007) claimed that the phosphorus consumed and that present in the urine are associated with the stabilization of the endogenous fecal loss, associated with the excess material ingested and the type of feed ingested, since the greater the effective fiber content ingested, the more salivation and excretion of phosphorus through the feces (Bravo et al, 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…for examples). Because most of this higher fluid throughput stems from saliva inflow into the digestive tract, this system has an increased potential to provide gastrointestinal microbes with additional nutrients, such as recycled nitrogen or phosphorus (Lapierre and Lobley, ; Bravo et al., ), possibly making ruminants somewhat less dependent on the nutrient influx via food intake.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kebreab and Vitti (2005), 45% of the total rumen P is recycled in saliva and many studies have shown that salivary P is in the inorganic form (Tomas, 1973;Scott and Buchan, 1987;Bravo et al, 2003). Although salivary secretion rate is affected by diet, concentration of Pi in saliva appears to remain constant (Tomas, 1973).…”
Section: The Rumenmentioning
confidence: 99%
“…Several models have been created to examine changes in P metabolism with dietary changes (Vitti et al, 2000;Bravo et al, 2003;Dias et al, 2006). However, these models have been created to interpret in vivo tracer kinetic data from small ruminants.…”
Section: Introductionmentioning
confidence: 99%